IIT-BHU In TREC 2018 Incidents Stream Track - Mehrotra H.; Pal S. (My University, 2025)
This paper presents details of the work done by the team of IIT (BHU) Varanasi for the Incidents Stream track in TREC 2018. The task involved classifying tweets posted during a disaster into a number of categories, which are useful for relief work purposes at such a time. The data given was in the form of tweets from one earthquake, tornado, wildfire, flood, shooting and bombing incident. © 2018 Copyright held by the owner/author(s).